2018
DOI: 10.1037/ccp0000304
|View full text |Cite
|
Sign up to set email alerts
|

The agreement between clients’ and their therapists’ ratings of personality disorder traits.

Abstract: When clinicians utilized systematic measures of dimensional traits their agreement with client was higher than reported in past studies. Furthermore, clients reported significantly more PD pathology than was noted by their therapists suggesting concerns about invalid self-reports due to underreporting have been overstated. (PsycINFO Database Record

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 46 publications
9
42
1
Order By: Relevance
“…It is likely that theories of accuracy from adaptive personality models would extend to the judgment of maladaptive personality traits. Agreement studies on maladaptive traits often find that disinhibition (i.e., maladaptive low conscientiousness), detachment (i.e., maladaptive low extraversion), and exhibitionism (e.g., maladaptive high extraversion traits) have the highest self-other agreement (Jopp & South, 2015;Keulen et al, 2011;Markon et al, 2013;Ready & Clark, 2002;Samuel, Suzuki, Bucher, & Griffin, 2018). This finding is consistent with studies on adaptive trait models showing higher self-other agreement on conscientiousness and extraversion (Connelly & Ones, 2010).…”
Section: Self-other Agreement On Ratings Of Personality Disorder Sympsupporting
confidence: 64%
See 1 more Smart Citation
“…It is likely that theories of accuracy from adaptive personality models would extend to the judgment of maladaptive personality traits. Agreement studies on maladaptive traits often find that disinhibition (i.e., maladaptive low conscientiousness), detachment (i.e., maladaptive low extraversion), and exhibitionism (e.g., maladaptive high extraversion traits) have the highest self-other agreement (Jopp & South, 2015;Keulen et al, 2011;Markon et al, 2013;Ready & Clark, 2002;Samuel, Suzuki, Bucher, & Griffin, 2018). This finding is consistent with studies on adaptive trait models showing higher self-other agreement on conscientiousness and extraversion (Connelly & Ones, 2010).…”
Section: Self-other Agreement On Ratings Of Personality Disorder Sympsupporting
confidence: 64%
“…Regarding maladaptive traits, Samuel et al (2018) found that clients generally rated themselves higher on maladaptive personality traits than their therapists rated them, particularly with regard to traits in the domain of psychoticism, which largely composes traits of schizotypal personality disorder. The effect was so large that it might reflect a misunderstanding of the psychoticism items on the part of the clients.…”
Section: Mean-level Agreementmentioning
confidence: 99%
“…Also, the external validity of conclusions is obviously contingent upon the extraction of the optimal number of profiles; it must be acknowledged that our retained four-profile solution was not completely unambiguous (as shown by other plausible alternatives; see Table 1 and Supplementary Figure 1). Data were mostly collected through self-report questionnaires, which comes with the risk of dishonesty and/ or poor insight in some cases; however, evidence supporting the validity and usefulness of self-ratings of personality pathology is accumulating [57], as most patients seem to report considerable levels of personality pathology through self-report assessment [58]. While filerated aggression showed meaningful distinctions among profiles, the absence of significant results for file-rated suicidality and self-harm might point to a lack of sensitivity of the scales designed to rate them, to a lack of power in contrast with other indicators and variables (as there were a number of missing data), or to an "authentic"-albeit surprising-absence of difference among profiles on these critical outcome variables.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of the present study is the sole reliance on self-reported variables as external validators. While evidence supporting the validity and usefulness of self-ratings of personality pathology is mounting [e.g., (74,75)], the impact of response style bias as a potential confounding variable could not be taken into account. Future investigations of the validity of the present degrees of severity should not only include multiple instruments, but also multiple methods, as well as longitudinal and behavioral outcomes assessment, most notably to assess the risk of harm to self and others.…”
Section: Discussionmentioning
confidence: 99%